A MAPbBr3:poly(ethylene oxide) composite perovskite quantum dot emission layer: enhanced film stability, coverage and device performance. Issue 18 (26th April 2019) - Yu, Hongtao; Lu, Yao; Feng, Zengqin; Wu, Yanan; Liu, Ziwei; Xia, Pengfei; Qian, Jie; Chen, Yanfeng; Liu, Lihui; Cao, Kun; Chen, Shufen; Huang, Wei
Abstract : MAPbBr3 :poly(ethylene oxide) composite perovskite quantum dots as the emission layer of LEDs significantly enhance film coverage, device stability and electroluminescence performances. Abstract : Metal halide perovskite quantum dots (PQDs) have become the most promising optoelectronic material in new generation displays and lighting devices due to their excellent optical properties. However, their stability and surface defects have affected their large-scale applications. We demonstrate enhanced stability of high-surface-area colloidal PQDs encapsulated with long-chain organic polymer poly(ethylene oxide) (PEO) via simply mixing the PQDs with this high molecular-weight polymer. The introduction of the polymer deactivates the surface defects of PQDs and sufficiently protects the organic ligands on the surfaces of PQDs with obviously improved ambient stability and photoluminescence quantum yield. Moreover, the use of PEO efficiently confines electrons within the PQD emission layer and generates extremely stable green electroluminescence spectra in MAPbBr3 light-emitting diodes (LEDs) over a wide voltage operation range of 5–12 V, accompanied by significant improvements in external quantum efficiencies with enhancement factors of 18.3 times. Our work provides a robust platform for the fabrication of stable PQDs, high-quality PQD films and efficient PQD-based LEDs.